Exports, trade policy and economic growth in eras of globalization - Feasel, Edward M., author.
1 online resource (242 pages)
Keywords: This book provides an excellent resource for understanding the forces in international trade liberalization over two centuries that have brought us to this point, where the successes, setbacks and the countervailing forces now vie for the public's mind and support: the outcome of which will determine the future progress of increased globalization, or lack thereof.The book also examines whether trade policy has indeed promoted exports in the vast number of countries which increasingly look to trade agreements to gain a competitive edge, and to what extent export-driven growth has been an important force in advancing economic development around the world. In doing so, the book examines one of the most controversial issues in economic development: the promotion and significance of export-led growth.